Challenges and Solutions for Handling and Characterizing Alkali-Tc-Oxide Salts. (8th February 2018) - Weaver, Jamie L.; Soderquist, Chuck; Washton, Nancy; Gassman, Paul; Walter, Eric; Bowden, Mark; Lukens, Wayne; McCloy, John S.
ABSTRACT: Though not often discussed explicitly in literature, sample handling and preparation for advanced characterization techniques is a significant challenge for radiological materials. In this contribution, a detailed description is given of method development associated with characterization of highly radioactive and, in some cases, hygroscopic oxides of technetium. Details are given on developed protocols, fixtures, and tooling designed for x-ray and neutron diffraction, x-ray absorption, Raman spectroscopy, magic angle spinning nuclear magnetic resonance, and electron paramagnetic resonance. In some cases, multiple iterations of improved sample holder design are described. Lessons learned in handling Tc compounds for these and similar characterization methods are discussed.